Resiliens i et globalt klimaperspektiv - Eskjær, Mikkel Fugl (Slagmark - Tidsskrift for idéhistorie, 2018)
Resilience has become a key concept in the global climate change discourse, not least in relation to climate change adaptation in the Global South. Taking Bangladesh as an example, this paper explores the role and function of resilience in one of the most climate vulnerable nations. The aim is to examine and critically discuss the popularity of resilience in recent climate change policy. The paper looks into the following aspects of climate change resilience: (i) the relation between resilience and the concepts of mitigation/adaptation; (ii) resilience as a re-description of existing socio-ecological means of adaptation; (iii) resilience as an example of the integration of climate change adaptation and development; (iv) resilience as a strategic resource in obtaining international climate change funding. The four aspects illustrate how the discourse of resilience is surrounded by rather diverse mechanisms and dynamics, which may account for the concepts popularity. It further indicates that while the concept promises a pro-poor and context sensitive approach to climate change resilience, it also risks effacing the principal differences between development and climate change adaptation.